Improving Communication and Collaboration Skills via e-Learning Contents - Rila Setyaningsih; Abdullah Abdullah; Edy Prihantoro; Hustinawaty Hustinawaty (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
Developing e-learning content at a boarding university needs communication and collaboration skills. This study aims to discuss the strategy of improving communication and collaboration skills via e-learning content. This study uses a descriptive qualitative method. Data were collected through observation and interviews with stakeholders and lecturers. This study found that the strategy of improving the communication and collaboration skills via e-learning contents at the boarding university is conducted through four stages. The four stages are access, analysis, evaluation, and content creation: (1) The access is made by lecturers and students at the University of Darussalam Gontor in the form of the ability to use and utilize e-learning models. (2) The analysis phase is in the form of the ability of lecturers to find, change, and select information relevant to the learning process. The analysis phase also deals with the verification step (tabayyun) of the accuracy of the information. (3) Evaluation is in the form of preparation of learning contents adjusted to the real conditions occurring in the community or referred to as contextual learning. (4) Development of learning content is applied to five basic courses in the Communication Studies Program.